Social Support among Nurses at Iran University of Medical Sciences - N Rezaee; M Ghajeh (Tehran University of Medical Sciences, 2009)
Background & Aim: Social support is known as a factor in buffering negative effects of occupational stress. There are several stressful situations in nursing which could cause job dissatisfaction, low work performance, quit or turnover among nurses. These situations cause physical and mental problems which mostly lead to irreparable damages in nursing care. The purpose of this study is to determine the rate of social support among nurses. Methods & Materials: In this cross-sectional study, 373 nurses who worked in Iran university of medical sciences affiliated hospitals were selected randomly. The inclusion criteria were nurses who had no management experiences and at least had a six-month nursing experience. Data were gathered using a demographic form and the McCain and Marklin Social Integration Scale. Data were analyzed using SPSS 13. Results: Eighty five percent of nurses mentioned that the support they receive from their coworkers, head nurses, and supervisors were moderate, high (10.7%), and low (4.3%), respectively. A significant association was found between social support and shifts. Perceived support from coworkers (mean=24.83) were more than perceived support from head nurses and the supervisors (mean=19.37). Conclusion: Most of the nurses received moderate level of support whilst, they desired to have more relationship with their coworkers and nurses managers. Head nurses and supervisors can arrange excursions and traveling tours to establish more relationship with their staff.